Subjective wellbeing of elderly people: social domain aspect - Vaznonienė, Gintarė (Social Welfare: Interdisciplinary Approach, 2014)
This article discloses the interrelations between social domain and subjective wellbeing of elderly people in Lithuania. The changes after the reestablishment of the independence of Lithuania challenged wellbeing differentiation in the society, which determined that some elderly people feel low wellbeing while others live normally. The influence of social domain on the subjective wellbeing among elderly people has shown that higher ratings of subjective wellbeing are based on strong social relations, family help in individual care while the state is a guarantee of financial resources, the level of social integration depends on the activity of various institutions as well as on different fears and social problems.